Mifepristone and misoprostol versus misoprostol alone in management of late intrauterine fetal death - Gupta, Shilpa; Kagathra, Bhumika; Desai, Ajesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The objective was to assess the efficacy and safety of pretreatment with Mifepristone in induction of late intrauterine fetal death in combination with misoprostol. Methods: A prospective study was carried out in GMERS Medical College, Sola, Ahmedabad between October 2014 to April 2016. Data from 72 women with intrauterine fetal death between the gestational age of 24 to 42 weeks were analyzed. Group A women received single oral dose of 200 mg Mifepristone followed 36 to 48 hours later with Misoprostol (200-50 microgram) every 4 hour to a maximum of 5 doses. The first dose was kept vaginally in the posterior fornix and the rest were given orally. The dose of Misoprostol depended upon the gestational age and the parity. Group B women received only Misoprostol. If the first cycle failed, then after a break of 24 hour, a second course of Misoprostol was started. Outcomes were measured in terms of induction to delivery interval and number of Misoprostol doses needed. Results: Maternal age, parity, gestational age and pre-induction bishop score were comparable in both the groups. Induction to delivery interval was shorter in the combination regimen. Total dose of Misoprostol needed was also less in the Group pretreated with Mifepristone. In group A 93.3% women delivered within 24 hours of first dose of misoprostol while in group B it was 80.5%. More women in group B required oxytocin. Regarding the complications during labor and delivery the two groups did not have major differences. Conclusions: Both regimens are safe for the induction of labour in late IUFD. However, the induction delivery interval and the dose of misoprostol needed was decreased by the pretreatment with Mifepristone.